2013
DOI: 10.1039/c2md20320k
|View full text |Cite
|
Sign up to set email alerts
|

Developing novel C-4 analogues of pyrrole-based antitubulin agents: weak but critical hydrogen bonding in the colchicine site

Abstract: The synthesis, biological evaluation and molecular modeling of a series of pyrrole compounds related to 3,5-dibromo-4-(3,4-dimethoxyphenyl)-1H-pyrrole-2-carboxylic acid that evaluates and optimizes C-4 substituents are reported. The key factor for microtubule depolymerization activity appears to be the presence of an appropriately positioned acceptor for Cys241β in the otherwise hydrophobic subpocket A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…We previously evaluated pyrrole C4 phenyl substituents and their interaction within the A pocket of the colchicine site. These modeling simulations and biological evaluation of 18 compounds with various phenyl substitutions at C4 identified the importance of hydrogen bonding between the compound and Cys241b, which is in an otherwise hydrophobic pocket (Da et al, 2013b). The refined model shows that the precise placement of hydrogen bond acceptors and hydrophobes in this pocket is critical: the 3-methoxyphenyl substituent at C4 has a five-fold higher EC 50 , and the 4-methoxyphenyl substituent has a 14-fold higher EC 50 than the 3,4-dimethoxyphenyl substituent found in JG-03-14 (Da et al, 2013a).…”
Section: Discussionmentioning
confidence: 97%
“…We previously evaluated pyrrole C4 phenyl substituents and their interaction within the A pocket of the colchicine site. These modeling simulations and biological evaluation of 18 compounds with various phenyl substitutions at C4 identified the importance of hydrogen bonding between the compound and Cys241b, which is in an otherwise hydrophobic pocket (Da et al, 2013b). The refined model shows that the precise placement of hydrogen bond acceptors and hydrophobes in this pocket is critical: the 3-methoxyphenyl substituent at C4 has a five-fold higher EC 50 , and the 4-methoxyphenyl substituent has a 14-fold higher EC 50 than the 3,4-dimethoxyphenyl substituent found in JG-03-14 (Da et al, 2013a).…”
Section: Discussionmentioning
confidence: 97%
“…Although taccabulin E ( 4 ) was calculated to have the third highest HINT binding score, its limited ability to inhibit tubulin polymerization suggests that the hydrogen bonding interactions with Thr179α and Val181α are more critical for binding than was anticipated by our modeling and that taccubulin E ( 4 ) appears to be less acceptable from Cys241β, which is a critical feature for strongly active compounds that is difficult to score. 16 …”
Section: Results and Discusionmentioning
confidence: 99%
“…1,2,3,4 In this study exposure to JG-03-14 reduced the production of pro-inflammatory molecules by macrophages activated with lipopolysaccharide (LPS). Treatment with the pyrrole-based compound decreased the concentration of tumor necrosis factor-α (TNF-α) and nitric oxide (NO) released from the macrophages.…”
mentioning
confidence: 84%
“…Earlier studies that demonstrated the importance of the C-2 and C-4 positions of JG-03-14 for tubulin binding also showed that the tubulin-depolymerizing property of this compound correlated with anti-proliferative activity in a wide range of cancer cell lines. 2,3 Further investigations demonstrated that JG-03-14 promotes autophagic cell death of tumor cells and that it is active against tumor cells expressing the multidrug resistance pump, providing additional support for the potential use of JG-03-14 to treat malignancies. 7,8 However, little is known about the effect of JG-03-14 on immune cells, specifically macrophages, which detect invading microorganisms in the tissues, carry out phagocytosis, and produce pro-inflammatory mediators.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation